Ternary wide-bandgap chalcogenides LiGaS2 and BaGa4S7 for the mid-IR (International Journal of Engineering and Computer Science, 2014)
In this work we study the parametric interaction at the presence of the phase change of interacting pump, signal and idler waves. It is considered in the materials of mid-infrared range of spectrum for LiGaS2 and BaGa4S7 crystals. The threshold intensity of pumping is analyzed for these crystals under the conditions of the experiments. The values of refractive indices and angle of phase matching have been calculated for these crystals. It is shown that LiGaS2 and BaGa4S7 compounds could be used for nanosecond/picoseconds pumping of optical parametric converters at 1.064 mcm (Nd:YAG laser systems) without considering two-photon absorption.